THU0275 SEVERE PREECLAMPSIA RELATED TO ANTIPHOSPHOLIPID SYNDROME: AN EUROPEAN STUDY OF 40 WOMEN. (2nd June 2020) - Larosa, M.; Morel, N.; Belhocine, M.; Ruffatti, A.; Silva, N. M.; Paul, R.; Mouthon, L.; Dreyfus, M.; Piette, J. C.; Souchaud-Debouverie, O.; Deneux-Tharaux, C.; Tsatsaris, V.; et al.
Abstract : Background: One of the 3 features of obstetrical antiphospholipid syndrome (APS) is severe preeclampsia (PE). Its time of occurrence, the associated risk of thromboses and systemic lupus erythematosus (SLE) have not been reported yet. Objectives: We analyzed severe PE in a series of women with APS. Methods: We retrospectively collected data of female patients from 5 French internal medicine and 1 Italian rheumatology units. Inclusion criteria were: a severe PE/eclampsia(1), that occurred before 34 weeks of gestation (WG) in patients who met the APS classification criteria(2). Results: 40 patients were enrolled (Table 1 ). Because of known APS/positive aPL/previous obstetrical complications, 23(57.5%) patients were treated during the index PE: 4 with low dose aspirin (LDA), 4 with low molecular weight heparin (LMWH), and 15 with a combination of both. 7 patients were also treated with hydroxychloroquine, 8 with corticosteroids and 3 with immunosuppressants. 17(42.5%) patients received no treatment. 24(60%) live births were observed. During a follow-up period of 3 years, 26(65%) patients had at least 1 new pregnancy, with a total of 38 pregnancies which resulted in 33(86.8%) live births. 57.5% pregnancies who resulted in live births occurred without any maternal or fetal complications. All 26 patients who had at least 1 pregnancy after index PE were treated with LDA; LMWH was given at prophylactic and therapeutic dosage in 13(50%) patients, respectively. No patient experienced 3 consecutive miscarriages. Conclusion: Among the APS criteria, "3 consecutive miscarriages criterion" was not found. The majority of patients also experienced thrombosis and SLE before the index PE. References: [1]Diagnosis and Management of preeclampsia and eclampsia. International Journal of Gynecology &Obestetrics 2002;77:67-75. [2]Miyakis S, et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost 2006;4:295e 306. Disclosure of Interests: Maddalena Larosa: None declared, Nathalie Morel: None declared, Meriem BELHOCINE: None declared, Amelia Ruffatti: None declared, Nicolas Martin Silva: None declared, Romain Paul: None declared, Luc Mouthon: None declared, Michel DREYFUS: None declared, Jean-Charles PIETTE: None declared, Odile Souchaud-Debouverie: None declared, Catherine Deneux-Tharaux: None declared, Vassilis Tsatsaris: None declared, Emmanuelle Pannier: None declared, Gaêlle Guettrot Imbert: None declared, Véronique LE GUERN Grant/research support from: UCB for GR2 study (to our institution), Andrea Doria Consultant of: GSK, Pfizer, Abbvie, Novartis, Ely Lilly, Speakers bureau: UCB pharma, GSK, Pfizer, Janssen, Abbvie, Novartis, Ely Lilly, BMS, Nathalie Costedoat-Chalumeau Grant/research support from: UCB to my institution